Modulating circulating sFlt1 in an animal model of preeclampsia using PAMAM nanoparticles for siRNA delivery. (October 2017) - Yu, Jun; Jia, Jing; Guo, Xijiao; Chen, Ruibao; Feng, Ling
Abstract: Introduction: Excessive circulating sFlt1 plays a major role in the pathogenesis of preeclampsia (PE). Using RNAi to silence sFlt1 may be a therapy for treating PE. Because of the rapid degradation of siRNA, gene therapy in vivo remains limited. Poly-amidoamine (PAMAM) has been demonstrated to be an excellent nanocarrier for siRNA delivery with no discernible toxicity. Methods: The aim of the present study was to investigate the therapeutic effect of siRNA-sFlt1-PAMAM on PE. The biophysical properties of siRNA-sFlt1-PAMAM complexes were analysed. Next, HTR-8/SVneo cells were incubated with the complexes. The transfection efficiency, silencing effect, and cell proliferation were examined. The timed pregnant rats were grouped to test the in vivo effect of siRNA-sFlt1-PAMAM on PE. The PE model was established by injection of tumour necrosis factor-α (TNF-α), while treatment group rats were injected with both TNF-α and siRNA-sFlt1-PAMAM. The mean arterial pressure, serum levels of sFlt1, and 24-h urinary protein were measured. The number of viable pups, and weights of individual pups and placentae were determined. Results: siRNA-sFlt1-PAMAM complexes showed high cellular uptake and excellent siRNA encapsulation ability. siRNA-sFlt1-PAMAM significantly decreased sFlt1 secretion from HTR-8/SVneo cells ( p  = 0.001) with little effect on HTR-8/SVneo cell proliferation. The circulating level of sFlt1, mean arterial pressure, and urine protein level in the TNF-α group were significantly increased compared to that in the control group, while the weights of foetuses and placentae were significantly decreased compared to that in the control group ( p  < 0.05). All preeclamptic symptoms were greatly attenuated by siRNA-sFlt1-PAMAM ( p  < 0.05). Conclusions: These data suggest that siRNA-sFlt1-PAMAM effectively decreased sFlt1 secretion and improved pregnancy outcomes in a preeclamptic rat model, which may provide a new therapeutic strategy for PE. Highlights: The sflt-1 secretion from HTR-8/SVneo cells was significantly decreased after sflt-1-siRNA-PAMAM incubation. The siRNA-sflt-1-PAMAM effectively decreased circulating levels of sFlt-1 in vivo . The siRNA-sflt-1-PAMAM effectively decreased mean arterial pressure and proteinuria which were increased by TNF-α. The siRNA-sflt-1-PAMAM well improved the pregnancy outcomes of PE induced by TNF-α.